(untitled) (GESTIÓN Y TENDENCIAS, 2020)
This article describes the "Sidecar Savings" voluntary savings program and its experience with the implementation of the "Jars" pilot version. In a single product, Jars combines an emergency savings account, with no restrictions on withdrawals, and a traditional pension savings account that does not allow withdrawals. This innovation aims to improve people’s well-being by promoting the accumulation of savings that enable them to better address their short- and long-term needs. The article closes with two reflections. First, the "Jars" product contains elements that could improve the design of Collective Voluntary Pension Savings (APVC). Second, creating a pension intelligence unit similar to "Nest Insight" would help improve the development and testing of initiatives aimed at increasing savings and improving pensions.